Formal Methods for Computational Systems Biology - Bernardo, Marco (Springer, 2017)
This volume presents the set of papers accompanying the lectures of the eighth International School on Formal Methods for the Design of Computer, Commu-nication, and Software Systems (SFM).This series of schools addresses the use of formal methods in computer science as a prominent approach to the rigorous design of computer, communication, andsoftware systems. The main aim of the SFM series is to offer a good spectrum of current research in foundations as well as applications of formal methods,which can be of help for graduate students and young researchers who intend toapproach the field.